Cell type-specific intervention of transforming growth factor beta/Smad signaling suppresses collagen gene expression and hepatic fibrosis in mice. - Inagaki, Y; Kushida, M; Higashi, K; Itoh, J; Higashiyama, R; Hong, Y; Kawada, N; Namikawa, K; Kiyama, H; Bou-Gharios, G; Watanabe, T; Okazaki, I; et al. (2005)
BACKGROUND and AIMS: Transforming growth factor beta and its intracellular mediators, Smad proteins, play important roles in stimulating collagen gene transcription and, thus, could be the targets for treating hepatic fibrosis. However, intervention of transforming growth factor beta/Smad signaling affects physiological signal transduction as well and may cause serious adverse effects on clinical application. Here we have attempted to suppress hepatic fibrosis by expressing a transforming growth factor beta/Smad antagonist selectively in collagen-producing cells only in the fibrotic liver. METHODS: Recombinant adenoviruses expressing either green fluorescent protein or a transforming growth factor beta/Smad signal repressor, YB-1, were injected into mice untreated or treated with carbon tetrachloride. Green fluorescent protein expression was analyzed under a confocal laser scanning microscope. Antifibrotic effects of YB-1 overexpression were examined by luciferase assays and histological examination with transgenic reporter mice. RESULTS: When the CAG expression unit was used as a control, green fluorescent protein was strongly expressed in a large number of hepatocytes in both normal and carbon tetrachloride-treated liver. In contrast, green fluorescent protein expression driven by a tissue-specific enhancer of the mouse alpha2(I) collagen gene ( COL1A2 ) was detected in activated hepatic stellate cells in carbon tetrachloride-induced fibrotic liver, but not in untreated normal liver. No green fluorescent protein fluorescence was observed in any other organs when the COL1A2 enhancer was used. Adenovirus-mediated YB-1 expression under the control of the COL1A2 enhancer significantly decreased COL1A2 promoter activity after carbon tetrachloride injection and subsequently suppressed the progression of hepatic fibrosis. CONCLUSIONS: These results validate a new concept of the therapy for hepatic fibrosis to achieve cell type-specific gene expression only in the fibrotic liver, with little damage to other organs.